2019
DOI: 10.1021/acscatal.9b01584
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Hydrogenations via Olefin Cobaltate and Hydride Intermediates

Abstract: Redox noninnocent ligands are a promising tool to moderate electron transfer processes within base-metal catalysts. This report introduces bis(imino)acenaphthene (BIAN) cobaltate complexes as hydrogenation catalysts. Sterically hindered trisubstituted alkenes, imines, and quinolines underwent clean hydrogenation under mild conditions (2−10 bar, 20−80°C) by use of the stable catalyst precursor [(Dipp BIAN)CoBr 2 ] and the cocatalyst LiEt 3 BH. Mechanistic studies support a homogeneous catalysis pathway involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 106 publications
(65 reference statements)
1
40
0
2
Order By: Relevance
“…These organometallic studies of metalate‐catalyzed reactions have also demonstrated the opportunities for catalyst tuning through the nature of the counterion. Co‐catalytic assistance of counterions can involve diverse modes of substrate or catalyst activation . Upon implementation of metal‐based cations, bimetallic catalysis mechanisms can be engineered.…”
Section: Methodsmentioning
confidence: 99%
“…These organometallic studies of metalate‐catalyzed reactions have also demonstrated the opportunities for catalyst tuning through the nature of the counterion. Co‐catalytic assistance of counterions can involve diverse modes of substrate or catalyst activation . Upon implementation of metal‐based cations, bimetallic catalysis mechanisms can be engineered.…”
Section: Methodsmentioning
confidence: 99%
“…Diese Untersuchungen metallkatalysierter Reaktionen haben auch die Möglichkeit der Feinabstimmung von Katalysatoren über die Art des Gegenions aufgezeigt. Die cokatalytische Unterstützung durch Gegenionen kann verschiedene Arten der Substrat‐ oder Katalysatoraktivierung beinhalten . Durch Einführung metallbasierter Kationen können bimetallische Katalysemechanismen entwickelt werden.…”
Section: Methodsunclassified
“…Die cokatalytische Unterstützung durch Gegenionen kann verschiedene Arten der Substrat-oder Katalysatoraktivierung beinhalten. [20][21][22][23] Durch Einführung metallbasierter Kationen kçnnen bimetallische Katalysemechanismen entwickelt werden. Die ausgeprägte Reaktivitätvon Magnesium gegenüber Lithiumorganoferraten in diesen Studien spiegelt die Dominanz von Grignard-Reagenzien als nukleophile Komponenten in eisenkatalysierten Kreuzkupplungen wider.…”
unclassified
“…[43][44][45] The redox lability of the Co-BIAN moiety, in particular, has led to its use in numerous catalytic applications. [46][47][48][49][50] While VT has not been observed experimentally in Co-BIAN systems, 24,51 its occurrence in three complexes with the general formula [Co(L NO ) 2 (BIAN)] (L NO = a Schiff base ligand, Chart S1 †) has been computationally predicted, involving an interconversion between low-spin (LS) Co III -BIAN •− and high-spin (HS) Co II -BIAN 0 forms. 52 However, the calculated [Co(L NO ) 2 (BIAN)] complexes are difficult to access experimentally as they each contain either an ancillary ligand that cannot be isolated because it self-reacts and/or a BIAN ligand that has never been reported.…”
Section: Introductionmentioning
confidence: 99%